Contextualizing Sustainability with Reference to Startups - Sharma, Khushboo; Mathur, Himendu Prakash (Prabandhan: Indian Journal of Management, 2022)
A wide array of sustainability definitions is available in literature but insufficiently support defining the sustainability of startups. To overcome this gap, the study synthesized the concept of sustainability from various angles. It identified constructs based on which 13 experts from academia and industry were interviewed, asking for their opinion on the concept. The respondents were approached through LinkedIn and mail for personal interviews. A semi-structured questionnaire was used as the research instrument, and interviews were held virtually. The interviews were transcribed further for thematic content analysis. The findings of the study suggested that the definition of sustainability in the context of a startup can be constructed on the following themes: value creation along with wealth creation, innovative business model, economic and social gains, ability to survive on own funds, resilience, consistent coverage of the cost of operations, overheads & on-costs, spatial and temporal extent. The paper is an original contribution that defines the path for future research in the area to explore factors affecting a startup's sustainability to reduce startups' high mortality rate.